Role of the Extracellular Signal-Regulated Kinase 1/2 Signaling Pathway in Ischemia-Reperfusion Injury - Kong, Tingting; Liu, Minghui; Ji, Bingyuan; Bai, Bo; Cheng, Baohua; Wang, Chunmei (Frontiers in Physiology, 2019)
Extracellular signal-regulated kinase 1/2 (ERK1/2), an important member of the mitogen-activated protein kinase family, is found in many organisms and participates in intracellular signal transduction. Various stimuli induce phosphorylation of ERK1/2 in vivo and in vitro. Phosphorylated ERK1/2 moves to the nucleus, activates many transcription factors, regulates gene expression, and controls various physiological processes, finally inducing repair processes or cell death. Abnormal activation of the ERK1/2 signaling pathway is closely related to development of ischemia-reperfusion injury (IRI). However, the effects of this signaling pathway and the underlying mechanism differ between various models of IRI. This review summarizes the ERK1/2 signaling pathway and the molecular mechanism underlying its role in models of IRI in the brain, heart, liver, kidneys, and other organs. This information will help to increase understanding of ERK signaling and to identify a potential therapeutic target for IRI.